First measurement of the CP-violating phase in B0s → ϕϕ decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review letters, 2013)
A first flavor-tagged measurement of the time-dependent CP-violating asymmetry in B0s→ϕϕ decays is presented. In this decay channel, the CP-violating weak phase arises due to CP violation in the interference between B0s−¯¯¯B0s mixing and the b→s¯ss gluonic penguin decay amplitude. Using a sample of pp collision data corresponding to an integrated luminosity of 1.0 fb−1 and collected at a center-of-mass energy of 7 TeV with the LHCb detector, 880 B0s→ϕϕ signal decays are obtained. The CP-violating phase is measured to be in the interval [−2.46,−0.76] rad at a 68% confidence level. The p value of the standard model prediction is 16%.